PENGARUH BANTALAN KARET TERHADAP MOMEN YANG TERJADI PADA LINK SLAB BETON - Andi Rahmat (TEKNISIA, 2019)
The use of link slab as a substitute for expansion joints is one of the innovations that can provide benefits for bridge life, user comfort, and maintenance cost efficiency. Link slab is a slab placed on the upper surface of the adjacent girder end which forms a continuous slab system with the slab deck. In the transition zone, link slab and girder are installed in hard rubber and soft rubber pads at some thick variations in each type of rubber. Moment on the link slab is obtained due to the effect of traffic load according to SNI 1725: 2016 with the condition of the link slab without and with rubber pads. The study of the use of link slab in this paper is carried out in a numerical approach on a finite element software-Abaqus. Link slab is modeled as a 3D solid model in compressive concrete variations. In this study, the addition of hard rubber pads on link slab can reduce the magnitude of moments compared to link slab without rubber pads. This is indicated by the percentage reduction moment between 39,20-83,42% on LS-1, LS-2, and LS-3 hard rubber pads with thichness 10 mm, 20 mm and 30 mm. While on link slab with soft rubber pads is found that moments are greater at the very thick pads  This is indicated by the percentage difference in moments between 198,26 – 244,58% on LS-1, LS-2, and LS-3 soft rubber pads with thickness 10 mm, 20 mm and 30 mm. This large difference is due to the effect of moment change from negative moments (initial conditions) to positive moments after the addition of soft rubber pads.